Current Concepts in Dental Implantology - Turkyilmaz, Ilser (IntechOpen, 2015)
Implant dentistry has changed and enhanced significantly since the introduction of osseointegration concept with dental implants. Because the benefits of therapy became apparent, implant treatment earned a widespread acceptance. Therefore, the need for dental implants has caused a rapid expansion of the market worldwide. Dental implantology continues to excel with the developments of new surgical and prosthodontic techniques, and armamentarium. The purpose of this book named "Current Concepts in Dental Implantology" is to present a novel resource for dentists who want to replace missing teeth with dental implants. It is a carefully organized book, which blends basic science, clinical experience, and current and future concepts. This book includes ten chapters and our aim is to provide a valuable source for dental students, post-graduate residents and clinicians who want to know more about dental implants.